Keharmonisan Rumah Tangga Melalui Seksual Dalam Teks Lontar Rahasya Sanggama - Wardana, I Kadek Agus (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2022)
Every couple certainly wants harmony in their household, but in a marriage it doesn't always run smoothly. Sexual intercourse can also lead to frustration and disappointment. Harmonization in household relations can also cause spirituality to experience a significant increase because harmony in the household has been fulfilled. To produce valid and reliable data, this research uses qualitative research methods. To produce logical data, this article performs several stages of data sorting in the form of: 1). Reducing data, 2). Display data, 3). Verify data and, 4). Interpret article data. Related references really support the validity of a scientific work, therefore library techniques are also used through literature exploration on Google Scholar. Lontar Rahasya Sanggama provides a lot of understanding about proper and correct procedures for intercourse. Family harmony often occurs because of sexual conflicts. Satisfaction in the household that has occurred recently, such indications have been happening for a long time, but many have turned to divorce. Lontar Rahasya Sanggama, which existed at that time, was considered as the best alternative solution in solving problems related to sexuality.